Manipur the glorious past - Sharma, Arun K. 1933- (Aryan Books Internat., 1994)
Scientific results of the excavation at Sekta in Manipur, India.
Keywords: Funde; Excavations (Archaeology) -- India -- Sekta; Altertümer; Indien; Manipur (India) -- Antiquities; Sekta (India) -- Antiquities; Manipur